William G. Bishop, Charter of the City of Brooklyn 192, § 15 (1877) - (:unkn) unknown (My University, 1877)
Ordinances of the City of Brooklyn § 15: It shall not be lawful for any person to have kegs of gunpowder, or cause to be kept in any store, storehouse, manufactory or other building within the city of Brooklyn, any quantity of gunpowder exceeding twenty-five pounds in weight, under the penalty of the forfeiture of the gun-powder and an additional penalty of fifty dollars; and all gunpowder which may be kept in any building within said city shall be kept in tin canisters, and said canisters shall, at all times, be kept securely closed, except when necessary for its delivery on sale.
Keywords: GUNPOWDER - STORAGE